Decentralised aid management today: Perspectives on an evaluation - Lars Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2023)
The paper considers different possibilities for an evaluation of Danish aid management by outlining major changes of international and Danish development co-operation over the last 20 years. It involves the discussion of aid management in general and in relation to pragmatic co-operation approaches in particular, as well as the investigation of particular elements of the management of Danish development co-operation. It concludes that Danish and international development co-operation has changed significantly, due partly to aid management being assessed differently today compared to 10-15 years ago. Notably, the Danish development co-operation has required new aid management approaches, as it changed its focus from relatively stable poor countries to a diversity of countries including many fragile situations. Thus, an evaluation of Danish aid management and of the current status of the significant decentralisation of aid management to the Danish embassies in the early 2000s can no longer be usefully undertaken based only on the principles of the Paris Declaration on Aid Effectiveness from 2005, but needs to include other evaluation criteria as well.
Keywords: 330; Danish development co-operation; aid management; decentralised aid management